2006
DOI: 10.1001/archpsyc.63.10.1079
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the Effect on Quality of Life of Second- vs First-Generation Antipsychotic Drugs in Schizophrenia

Abstract: In people with schizophrenia whose medication is changed for clinical reasons, there is no disadvantage across 1 year in terms of quality of life, symptoms, or associated costs of care in using FGAs rather than nonclozapine SGAs. Neither inadequate power nor patterns of drug discontinuation accounted for the result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
582
5
19

Year Published

2006
2006
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,022 publications
(631 citation statements)
references
References 35 publications
25
582
5
19
Order By: Relevance
“…The clinical literature has generally reported no consistent, substantial improvement in cognition (at best only a marginal improvement) with the current pharmacotherapies for schizophrenia (Harvey and McClure, 2006;Keefe et al 2007). Indeed, we have conducted our own meta-analysis of the literature and found that total PANSS score improvement was not statistically greater with second-generation antipsychotics (SGAs) when compared with the first-generation antipsychotic (FGA), haloperidol (Tomes, unpublished observations), which is in agreement with findings of the recent CUtLASS study (Jones et al 2006). Cognition was not assessed in our analysis but this provides further evidence for the urgent need for improvement in therapy.…”
Section: Introductionsupporting
confidence: 83%
“…The clinical literature has generally reported no consistent, substantial improvement in cognition (at best only a marginal improvement) with the current pharmacotherapies for schizophrenia (Harvey and McClure, 2006;Keefe et al 2007). Indeed, we have conducted our own meta-analysis of the literature and found that total PANSS score improvement was not statistically greater with second-generation antipsychotics (SGAs) when compared with the first-generation antipsychotic (FGA), haloperidol (Tomes, unpublished observations), which is in agreement with findings of the recent CUtLASS study (Jones et al 2006). Cognition was not assessed in our analysis but this provides further evidence for the urgent need for improvement in therapy.…”
Section: Introductionsupporting
confidence: 83%
“…Reductions in GABAergic interneurones in these areas have been found in post-mortem analysis from patients with schizophrenia (Benes et al, 1991;Benes and Berretta, 2001;Beasley et al, 2002;Zhang and Reynolds, 2002). We have shown that atypical but not classical antipsychotics can reverse these cognitive deficits; however, in the clinic there is differing evidence for the efficacy of atypical antipsychotics in improving cognition with the CATIE study (Lieberman, 2006;Keefe et al, 2007) and the UK Cost Utility of the Latest Antipsychotic Drugs in Schizophrenia Study (CUtLASS; Jones et al, 2006; suggesting that antipsychotics actually have a limited effect. Cognitive dysfunction is a core characteristic of schizophrenia (Sullivan et al, 1994;Elvevag and Goldberg, 2000;Kuperberg and Heckers, 2000), occurring in 75-85% of patients (Reichenberg et al, 2006), and is becoming increasingly important as impaired cognition has been implicated in poor long-term functional outcome (Marder and Fenton, 2004) which can often persist when other symptoms may be improved with treatment (Gold et al, 1991;Heinrichs, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…In comparison to adult schizophrenia trials, these findings suggest that youth are less likely to maintain the same treatment over one year. [14][15][16][17] In addition, symptom response tended to plateau during maintenance therapy, such that most youth did not make significant improvements beyond what they had achieved at 8 weeks of acute treatment.…”
Section: Discussionmentioning
confidence: 99%